Characteristics of Heart Failure Patients Undergoing Intensive Care at Ibnu Sina YW-Umi Makassar Hospital in 2023 - Darussalam, A. Muh Nurdiansyah; Sommeng, Faisal; Abdullah, Rezky Putri Indarwati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Heart failure is a non-communicable disease which is the number one cause of death every year. Heart failure is caused by several avoidable and unavoidable factors. The prevalence of heart failure patients fluctuates from year to year. Considering the high incidence of heart failure, this research was conducted to identify the characteristics of heart failure patients at Ibnu Sina Hospital Makassar in 2023. The type of research is descriptive observational. Data were analyzed via Microsoft EXCEL and presented in table form. The research results showed that the majority of heart failure patients were aged 46 – 65 years in the adult category and were male. Heart failure patients have no history of smoking, no history of diabetes mellitus, and no hypertension. The majority of patients have a history of the cause category Coronary Artery Desease (CAD). Description of the death rate in heart failure patients as many as 9 people. The conclusion is that heart failure occurs at the age of 46 – 65 years and the majority are male with factors causing Coronary Artery Disease (CAD). Further studies need to be carried out in order to obtain fairly representative data.